Association of Polymorphisms of Metabolism-Related Genes with Psoriasis Vulgaris in Han Chinese. (20th September 2021) - Liu, Yu; Li, Xin; Huang, Yan-Ping; Cui, Zi-Yu; Bao, Jia; Zhang, Xue-Li; Guo, Yan; Su, Min-Jing; Lv, Xin-Xiang; Han, Jian-Wen
Abstract : Aim . Psoriasis is a chronic inflammatory disease with a complex etiology, and psoriasis vulgaris (PsV) is the most common type of psoriasis. Recent studies suggest the relationship between psoriasis and metabolic syndrome in different ethnicities. This study is aimed at evaluating the association of metabolism-related gene variants with the risk of PsV in Chinese Han population. Material and Methods . PsV patients (1030) and healthy controls (965) were enrolled in this study. Eighteen single-nucleotide polymorphisms (SNPs) previously reported to be significantly associated with metabolic syndrome were selected. SNPs were detected by next-generation sequencing. Results . Seven SNPs were significantly associated with PsV: rs805303 (P = 0.012, OR = 0.85 ), rs3177928 (P = 1.37 × 10 − 15, OR = 2.51 ), and rs2247056 (P = 3.73 × 10 − 4, OR = 0.67 ) located in the HLA gene region; rs1047781 (P = 0.012, OR = 1.18 ), rs281379 (P = 0.014, OR = 1.71 ), and rs492602 (P = 0.005, OR = 1.86 ) located in the FUT2 region; and rs2303138 (P = 0.014, OR = 1.18 ) located in the LNPEP region. After stratified analysis, rs805303 (P = 0.017, OR = 0.74 ) and rs2303138 (P = 0.041, OR = 1.30 ) were associated with PsVs when HLA-C ∗ 06 : 02 was positive, and rs805303 (P = 5.62 × 10 − 5, OR = 0.68 ), rs3177928 (P = 0.003, OR = 1.75 ), rs281379 (P = 0.034, OR = 1.96 ), and rs492602 (P = 0.025, OR = 2.04 ) were associated with PsVs when HLA-C ∗ 06 : 02 was negative. Conclusion . PsV and metabolic syndrome may have overlapped susceptible genes in Chinese Han population.